Developing Materials for EFL University Students’ Listening Comprehension Using Podcast - Yuli Qoumim Mahmudah (Universitas Negeri Surabaya, 2024)
This research is aimed to develop an ideal EFL university students’ listening worksheet to support the enhancement of their listening comprehension using Podcast as the audio source. This was an educational design research study involving the iterative cycle of analysis and exploration; design and construction; and also, evaluation and reflection. To conduct the study, the researcher had to analyze and explore the real problem which was encountered by the educational practitioners or students. The researcher used open-ended questionnaire as the instrument to analyze the problem. The researcher found that the EFL university had faced the problem dealing with their listening comprehension skill. After that, the design and construction phase were done to construct an intervention as the solution to the real problem. The researcher designed a listening comprehension worksheet using podcast as the media or the audio source as the intervention which was designed based on the students’ needs encountered on analysis and exploration phase. Then, the designed worksheet was through some process of evaluation and revision processes in evaluation and reflection phase. After the evaluation of the processes, the product or intervention was through the empirical testing to test its practical value. The result reflects that the designed worksheet is ideal to support the enhancement of EFL university students’ listening comprehension skill.